The Impact of Work Culture and Work Environment on Employee Performance: A Study at PT Pelindo Daya Sejahtera: Pengaruh Budaya Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan: Studi pada PT Pelindo Daya Sejahtera - Mudayat Mudayat; Oval Shobri Cahyana (Academia Open, 2023)
This research aims to investigate the influence of workplace culture and environment on employee performance at PT Pelindo Daya Sejahtera. The study employed a random sampling technique, with a sample size of 72 respondents comprising management employees from the company's headquarters and the East Java region. Data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, and simultaneous F-tests. The research findings confirm the validity and reliability of the indicators used. The classical assumption tests revealed normal data distribution without symptoms of heteroscedasticity or multicollinearity. The results indicate that both workplace culture (X1) and environment (X2) significantly affect employee performance. Additionally, the simultaneous influence of workplace culture and environment on employee performance is evident. These findings contribute to the understanding of the importance of fostering a conducive culture and work environment to enhance employee performance. The implications of this research can guide organizations, particularly in the maritime industry, to create supportive work environments and cultivate positive cultural values to optimize employee performance. Highlight: The study examines the influence of work culture and work environment on employee performance in PT. Pelindo Daya Sejahtera. Both work culture (X1) and work environment (X2) significantly affect employee performance (Y) in PT. Pelindo Daya Sejahtera. The findings suggest that fostering a conducive work culture and environment can enhance employee performance in the company. Keyword: Work Culture, Work Environment, Employee Performance, PT Pelindo Daya Sejahtera, Management Employes